Penerapan E-Module Berbasis Problem Based Learning untuk Meningkatkan Literasi Sains dan Mengurangi Miskonsepsi pada Materi Ekologi Siswa Kelas X MIA 6 SMAN 1 Karanganom Tahun Pelajaran 2014/2015 - IMANINGTYAS, CITRA DEVI; KARYANTO, PUGUH; NURMIYATI, NURMIYATI; ASRIANI, LILIK (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2016)
This research aims to increase the scientific literacy and decrease the student’s misconception in class X MIA 6 of SMAN 1 Karanganom by applying e-module based on the concept of Problem Based Learning (PBL). The type of the research is a classroom action research which consist of two cycles. Each cycles applied: planning the learning activity, then implementing those plan, next was observing the students’ activity and finally complimenting the whole activities during a cycle. The research subject is the students of class X MIA 6 at SMAN 1 Karanganom. There are 11 boys and 23 girls. The data validation used triangulation method. The data of the research were obtained by formulating the test, the observation and the interview. The obtained data were analyzed using the descriptive technique. The results of the research showed the implementation of e-module based on the concept of PBL decrease the students’ misconception on the ecology subject with the explanation: the population concept decreased 21%, the comunity concept run into reduction 22%, the ecosystem concept went down 21% and the ecology concept in ‘Science, environment, technology, and society’ context reduced 26%. The analysed result also indicated that the scientific literacy has increased 20.6%. The result of the research evidenced that implementation of e-module based on the concept of PBL could increase the scientific literation and decrease the students’ misconception on the ecology subject. Keywords: E-module with based Problem Based Learning, misconception, scientific literacy